Observation of hydrogen induced intermediate borides in PrFeB based alloys by Mössbauer effect spectroscopy - Saccone, Fabio Daniel (2002)
In the present work, a quantitative analysis of the phase compositions by Mössbauer effect spectroscopy of solid and conventional hydrogen disproportionated Pr13.7Fe80.3B6.0 and Pr13.7Fe63.5Co16.7Zr0.1B6.0 alloys was carried out. Significant amounts of intermediate borides t-Fe3B and Pr(Fe,Co)12B6 were detected after solid hydrogen disproportionation treatment in Pr13.7Fe80.3B6.0 and Pr13.7Fe63.5Co16.7Zr0.1B6.0 alloys, respectively. After conventional hydrogenation-disproportionation-desorption-recombination treatment these phases were not detected and in no case residual Pr2Fe14B-phase was found. It was observed that the amount of intermediate borides after disproportionation can be correlated with the degree of texture after recombination at various temperatures.